Social Dreaming for Social Justice: Power and Resistance in Chaos Walking. (4th May 2021) - Love, Jeannine M.; Fox, Charity
Abstract : Advancing social justice requires that public administration students, practitioners, and scholars engage in critical analyses of systemic power relations. To do so means grappling with questions of power, privilege, and oppression. This paper argues that the alternative worlds of speculative fiction offer spaces in which to explore the wicked problems facing humanity, examine oppressive power dynamics, and envision creative and liberatory solutions. These texts push readers to critique the structural injustices within their fictional worlds, examining ways that power functions and imagining possibilities for sociopolitical transformation. Offering a close reading of Patrick Ness' Chaos Walking trilogy, we argue that young adult dystopian fiction, a subgenre of speculative fiction, can serve as a tool for developing the theory competency necessary to engage in systemic power analyses. This paper examines the text through four types of power: power-over, power-within, power-to, and power-with. We conclude that sustainable, socially just outcomes cannot be achieved by shifting, dividing, balancing, or reclaiming power as a zero-sum resource. We must instead reconceive power as emergent, generative, and co-creative. This task requires fundamentally reconsidering our interconnections with one another and the world we inhabit; young adult dystopian fiction provides one tool for doing so.